Surgical versus endovascular intervention for vascular access thrombosis: a nationwide observational cohort study. Issue 9 (9th February 2022) - Lundström, Ulrika Hahn; Welander, Gunilla; Carrero, Juan Jesus; Hedin, Ulf; Evans, Marie
ABSTRACT: Background: There is no consensus whether an arteriovenous (AV) access thrombosis is best treated by surgical or endovascular intervention. We compared the influence of surgical versus endovascular intervention for AV access thrombosis on access survival using real-life data from a national access registry. Methods: We included patients from the Swedish Renal Access Registry (SRR-Access) with a working AV access undergoing surgical or endovascular intervention for their first thrombosis between 2008 and 2020. The primary outcome was the risk of access abandonment (secondary patency at 30, 60, 90 and 365 days). Secondary outcomes were time to next intervention and 30-day mortality. Access characteristics were obtained from the SRR-Access and patient characteristics were collected from the Swedish Renal Registry. Outcomes were assessed with multivariable logistic regression and Cox proportional hazards regression models adjusted for demographics, clinical and access-related variables. Results: A total of 904 patients with AV access thrombosis (54% arteriovenous fistula, 35% upper arm access) were included, with a mean age of 62 years, 60% were women, 75% had hypertension and 33% had diabetes. Secondary patency was superior after endovascular intervention versus surgical (85% versus 77% at 30 days and 76% versus 69% at 90 days). The adjusted odds of access abandonment within 90 days and 1 year were higher in the surgical thrombectomy group odds ratio (OR) 1.44 [95% confidence interval (CI) 1.05–1.97] and OR 1.25 (0.94–1.66), respectively. Results were consistent in the long-term analysis. There was no significant difference in time to next intervention or mortality, and results were consistent within subgroups. Conclusions: Endovascular intervention was associated with a small short- and long-term benefit as compared with open surgery in haemodialysis patients with AV access thrombosis. Graphical Abstract: